Usulan Perbaikan Laboratorium Komputer Universitas Ma Chung pada Aspek Suhu dan Pencahayaan dengan Pendekatan Ergonomi Partisipatori - Jovita Febrini Lius; Teguh Oktiarso; Novenda Kartika Putrianto (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
This study focuses on assessing the comfort of students when using computer laboratories at Universitas Ma Chung, particularly in terms of temperature and lighting. Using the participatory ergonomic approach, a comfort questionnaire was administered to students, with a total of 13 questions covering three indicators: room temperature, room lighting, and LCD. The questionnaire results were then tested using validity, reliability, and normality tests. The findings reveal that temperature and lighting do indeed have an impact on the level of comfort experienced by students when using a computer laboratory. These results have implications for campus facilities management and suggest the need for improvements to the temperature and lighting conditions in computer laboratories to enhance the comfort and well-being of students. By using the participatory ergonomic approach, this study provides valuable insights into the importance of considering user comfort in the design and management of campus facilities.